O uso do bambu: o papel da cadeia produtiva no setor moveleiro e da construção civil no Brasil - Tedeschi, Samara Pereira (2011)
The bamboo is a material widely used in Asia and its applications are from the simple fences to the Demoiselle structure, from Santos Dumont. In Brazil the bamboo uses still are small when it is compared to asian countries like China, that builds bridges to the bamboo floor. The bamboo productive chain can support the interrelation between the actors, making easier the information change and reinforcing the market, making it dynamic and competitive. The main goal of this research is the bamboo productive chain collect, identification and mapping in Brazil returned to the furniture industry, the construction and the potentiality relationship to the sustainable development. In this research will be collected and identified the environment where the productive chain actors are inserted through the patent search, institutes and universities, available credit and financing lines, environmental certification, laws and standards that regulate the sector, besides the questionnaires to the farmers, bamboo processors companies and those that produces consumer goods, besides the Non- Governmental Organizations. To the patent search were used the patent databases Derwent Innovations Index, Espacenet, United States Patent and Trademark Office and the Instituto Nacional de Propriedade Intelectual, through the use of search expressions and arrange with International Patent Classification. The universities and Institutes that research about bamboo were identified through the Conselho Nacional de Desenvolvimento Científico e Tecnológico website. The credit and financing lines collect were made through the Ministério do Meio Ambiente in the Serviço Florestal Brasileiro by the Guia de Financiamento Florestal 2010 and also by the website from the Sociedade Brasileira de Silvicultura; while the certification survey was made also through the websites from the Sociedade Brasileira de Silvicultura and Instituto Nacional de Metrologia. The laws and standards that regulate the sector were identified through the website from the Ministério do Trabalho e do Emprego, Associação Brasileira de Normas Técnicas and bibliographic references. The perceptions about the bamboo productive chain actors were analyzed after the questionnaires. The searches held in the patent databases showed the chineses are those that more deposit patents, and it directly related to the tradition of the material use. Behind are the japoneses, north-americans anda Canadians, and there is a small contribution of brazilian patents. The research about the material has been done by 13 universities and 4 institutes. However the credit and financing lines are 7, but are used widely to the eucalyptus and pinus forests. The certification in Brazil can be obtained through by the certification agencies that represent the Forest Steward Council, CERFLOR and OCIA Organic. The bamboo can be used in the Furniture Sector and in the Construction as a structural material, because besides of its strong sustainable appeal there is the question of his so low cost. A lot of companies uses the bamboo as a handicraft, but it are marketed as a product with a higher added value through its processing, that still is recent in the country. On the research field in Brazil there is still much to be done, when compared to world leaders in bamboo production, because the material is the subject of research for nearly two decades in Brazil and has grown significantly after the year 2000. The future perspective is to assure that a wider dissemination of the material, breaking paradigms and prejudices that exist in Brazilian society.